California's Public Schools A Needs Assessment. - California State Legislature, Sacramento. Joint Legislative Audit Committee; California State Legislature, Sacramento. Joint Legislative Audit Committee ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
This report is based on surveys of unified school districts, elementary school districts, high school districts, county offices of education, and state special schools in California. Performed by the Joint Legislative Audit Committee (JLAC), the document provides the state legislature an assessment of the facility and personnel needs facing California's schools as reported by the districts themselves. In assessing how personnel and facility needs differ among districts, the JLAC divided districts into 6 groupings based on average daily attendance. After describing the methodology, the report provides a breakdown of the needs and costs of administrators, teachers, classified personnel, and facilities. Among the findings, schools reported a need for 484.63 administrators, 9,204.75 additional teachers, and 3,302.43 more classified positions to maintain current levels of service. To maintain current services, districts reported it would cost over $18 million; the implementation of anticipated improvement would cost over $24 million. Also, all school districts reported that the class-size reduction program displaced other programs. The report discusses the need for emergency permits, for additional classrooms, the availability of sites for school construction, child development and child care, and joint-use facilities. An appendix provides more information on displaced programs and other needs. The survey instrument appears at the back. (RJM)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Assessment; Elementary Secondary Education; Financial Needs; Needs Assessment; Public Schools; State Aid; State Surveys; Summative Evaluation; California; Numerical/Quantitative Data; Reports, Research; Tests/Questionnaires.